Analitik SDM dan Big Data: Transformasi Manajemen Talenta dan Perencanaan Tenaga Kerja di Ekonomi Digital - Nur Hikmah Handayani; Nayra Shiva Salsadila; Wanti Wulandari; Mada Aditia Wardhana (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2026)
This article examines the transformative application of HR Analytics and Big Data (BD) in human resource management in the digital era, particularly their impact on the effectiveness of Talent Management (TM) and Workforce Planning (WP). This systematic literature review aims to analyze how ethical constraints, privacy, and algorithmic bias moderate this relationship, and explore strategies for leveraging data to build organizational agility and resilience. The study reveals that while HR Analytics and BD enhance proactivity and accuracy in TM and WP, ​​their effectiveness is significantly moderated by ethical challenges and bias, particularly in resource-constrained environments such as MSMEs and startups. It concludes that realizing the full benefits requires a responsible analytics approach that integrates data governance, bias auditing, and HR literacy. This research provides recommendations for practitioners, policymakers, and a future research agenda.